2022
DOI: 10.1002/lary.30324
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vocal Boost Manipulations on Musical Sound Quality for Cochlear Implant Users

Abstract: Objective To evaluate the impact of vocal boost manipulations on cochlear implant (CI) musical sound quality appraisals. Methods An anonymous, online study was distributed to 33 CI users. Participants listened to auditory tokens and assessed the musical quality of acoustic stimuli with vocal boosting and attenuation using a validated sound quality rating scale. Four versions of real‐world musical stimuli were created: a version with +9 dB vocal boost, a version with −9 dB vocal attenuation, a composite stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The CI users generated mixes that showed a relatively more intensive adjustment of the voices. In line with this is the recent study by Limb et al (2022) who showed that music was preferred by CI users when the voice of the sound was amplified by 9 dB – a value that is in the range of the gain-steps adjusted in the present study (see Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…The CI users generated mixes that showed a relatively more intensive adjustment of the voices. In line with this is the recent study by Limb et al (2022) who showed that music was preferred by CI users when the voice of the sound was amplified by 9 dB – a value that is in the range of the gain-steps adjusted in the present study (see Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…For music with lyrics, vocal information is often essential for understanding the story and themes of a song, making it an inextricable aspect of the music. As vocal components of music are often contained within mid-range frequencies (defined as 501-2,000 Hz in the present study), FRM that boost this frequency range might help to augment CI-mediated musical sound quality due to the increased clarity and intelligibility of speech information (Limb et al, 2022).…”
Section: Introductionmentioning
confidence: 93%
“…Cochlear implants (CI) are surgically implanted devices that restore partial sound and speech perception to individuals with severe-to-profound sensorineural hearing loss (Carlson, 2020;Gaylor et al, 2013). While these devices have been shown to significantly improve speech perception in quiet environments (Wilson & Dorman, 2008), the processing of complex sounds such as music is severely limited (Limb, 2006). Sound quality is significantly diminished for CI users compared to normal-hearing listeners (Lassaletta et al, 2008a(Lassaletta et al, , 2008bRoy et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers proposed using schemes to reduce spectral complexity (27)(28)(29)(30) and remixing music based on the preferences of CI recipients (31)(32)(33)(34). In various studies, the most consistent and critical finding of previous studies is that CI recipients preferred larger vocals to instrument ratio in songs ranging from 3 to 15 dB (31), 1.92 and 3.82 dB on average (33), and 8-9 dB on average (34,35). This common observation is intruding considering the importance of human voice and lyrics in modern music.…”
Section: Introductionmentioning
confidence: 99%